Benin : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2008)
Benin's Fifth Review under the Poverty Reduction and Growth Facility and request for waiver of Nonobservance of Performance Criteria are discussed. The main challenge ahead is to limit inflation pressures from higher food and fuel prices while sustaining medium-term fiscal consolidation and accelerating structural reforms to increase the sustainable growth rate. The authorities have taken actions to address the food and fuel crisis and accelerate structural reforms. They have allowed the full pass-through of higher international food and fuel prices and tightened fiscal policy while putting in place measures to protect the poor.